DOI: 10.11606/t.11.2001.tde-26072002-165831
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da nebulização e abertura de cortinas na redução da temperatura do ar em ambiente protegido.

Abstract: Ao professor orientador Dr. Marcos Vinícius Folegatti, por ter participado durante todo o processo de elaboração e execução desse trabalho sempre com muita dedicação, incentivo e amizade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
16

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
16
Order By: Relevance
“…The black globe temperature was measured using a globethermometer, which was installed in each barn. Data were recorded once weekly at 09.00, 13.00, and 17.00 h. Black globe humidity index (BGHI) and enthalpy were calculated according to Buffington et al (1981) and Villa Nova (1999) apud Furlan (2001) Egg production and mortality rates were evaluated daily. With regard to the study of poultry behavior, the obtained data were grouped as follows: physiological behaviors, reproductive behaviors, undesirable and agonistic behaviors, and behaviors indicative of welfare (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The black globe temperature was measured using a globethermometer, which was installed in each barn. Data were recorded once weekly at 09.00, 13.00, and 17.00 h. Black globe humidity index (BGHI) and enthalpy were calculated according to Buffington et al (1981) and Villa Nova (1999) apud Furlan (2001) Egg production and mortality rates were evaluated daily. With regard to the study of poultry behavior, the obtained data were grouped as follows: physiological behaviors, reproductive behaviors, undesirable and agonistic behaviors, and behaviors indicative of welfare (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Guiselini and Sentelhas (2004) observed that the minimum RH during the daytime period was influenced by the plastic covers, because during the day the saturation water vapor pressure (es) inside the greenhouses reached values above those observed outside, which resulted in a lower RH, even with an increase of actual vapor pressure (ea) caused by the retention of water vapor by the plastic cover (Buriol et al, 2000;Furlan, 2001;Viana, 2000). The daily variation of average air temperature (°C) over the three tomato growing seasons showed very similar results, except for days from 9/19/08 to 9/23/08 in the 1 st period, in which the outside average temperatures were far below to those observed inside the greenhouses.…”
Section: Resultsmentioning
confidence: 99%
“…Depende, portanto, dos processos de incidência da radiação solar, reflexão e re-irradiação através dos objetos no interior da estufa, convecção e condução através da cobertura e paredes, renovação do ar, evapotranspiração e troca de calor com o solo (Cermeño, 1993). A renovação de ar por meio de ventilação natural através da abertura de janelas e cortinas possibilita reduções significativas na temperatura no interior de estufas de polietileno (Furlan, 2001).…”
Section: Temperatura Do Arunclassified
“…A cobertura plástica utilizada em estufas é responsável por alteração significativa no balanço de radiação que ocorre em seu interior, em relação ao ambiente externo, devido à atenuação causada pela cobertura na radiação solar incidente, o que acaba resultando em redução no saldo de radiação interno (Furlan, 2001) e, conseqüentemente, na evapotranspiração. Assim, no interior de estufas a evapotranspiração é, geralmente, menor do que aquela que ocorre no ambiente externo, devido não somente à redução no saldo de radiação, mas também à menor ventilação e à maior umidade do ar (Pereira et al, 2002).…”
Section: Evapotranspiraçãounclassified
See 1 more Smart Citation